Folklife Annual, 1986 - Library of Congress, Washington, DC. American Folklife Center; Jabbour, Alan; Hardin, James; Library of Congress, Washington, DC. American Folklife Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Folklife is the study of tradition, of what carries forward through time, providing continuity and identity with a place or an activity. This collection of articles is intended to provide a forum for the discussion of theories and procedures of folklife study and to demonstrate both the variety of folklife communities and the unexpected similarities displayed by seemingly disparate groups or situations. "Breakdancing" (S. Banes) traces the phenomenon of breakdancing from its origins on the streets of New York City in the early 1980s where it served as a nonviolent form of competition between gangs, or "crews," of youngsters through its transformation into a theatrical event. "Among the Qeros" (J. Cohen) details the return visit of a filmmaker to a remote region in the Andes of Peru and the changes he found there after only six months. "'Bleows'": The Whaling Complex in Bequia" (H. P. Beck) describes 19th century whaling customs still practiced on the island of Beguia in the Lesser Antilles. "The Kalevala: 150 Years, 1835-1985" (E. Brodunas) introduces this Finnish folk epic. "The Kalevala Process" (L. Honko) discusses the history of the epic, and "Partial Repentance of a Critic: The Kalavala, Politics, and the United States" (W. A. Wilson) is a critic's reassessment of The Kalevala. "Immigrant to Ethnic" (Y. H. Lockwood) has to do with the symbols of identity among Finnish Americans. "Minnesota Logging Camp, September 1937" (R. Lee) is a photographic essay. "Via Dolorosa" (A. Asplund) is the life story of a Finnish immigrant to the United States, and "Symposium on the Life Story" (E. D. Ives, et al.) provides commentary on the preceding article. Many black and white and color photographs are included. (JB)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, DC 20402.
ERIC Note: For the 1987 edition, see SO 020 180.
Microfiche.
Keywords: Cultural Education; Dance; Ethnic Groups; Ethnography; Folk Culture; Foreign Countries; Foreign Culture; Legends; Mythology; Photographs; Breakdancing -- Finland -- Finnish Americans -- Peru -- West Indies; Books; Historical Materials